2019
DOI: 10.1177/1465312519879934
|View full text |Cite
|
Sign up to set email alerts
|

National British Orthodontic Society (BOS) Orthognathic Audit 2017–2018

Abstract: Objective: To carry out a UK national clinical audit of orthognathic acceptance criteria and information provided to orthognathic patients before treatment. Design: National clinical audit. Setting: Data collected using Bristol Online Surveys. Participants: Sixty-nine UK hospital orthodontic departments submitted data. Methods: Data were collected at two time points using Bristol Online Surveys over a period of 12 months. These were before treatment at the first multidisciplinary clinic (MDT) and immediately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The national orthognathic audit 2017–2018 reported a broad range of waiting time (range <1 month to 4 years) from immediate preoperative MDT to surgery ( Ireland et al, 2019 ). Consistent with this, a longer waiting list/waiting time was a weakness of some of the orthognathic MDT clinics in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The national orthognathic audit 2017–2018 reported a broad range of waiting time (range <1 month to 4 years) from immediate preoperative MDT to surgery ( Ireland et al, 2019 ). Consistent with this, a longer waiting list/waiting time was a weakness of some of the orthognathic MDT clinics in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A marked variation in the orthognathic care pathway has been reported ( Morris, 2006 ; Parbatani et al, 2010 ) and confirmed via a questionnaire study preceding this study by the same team. Further, Ireland et al (2019) analysed the acceptance criteria, information provision and attendance of MDT clinics by orthognathic patients in an audit. This audit reported that 3.07% of patients had not been through the pre-treatment MDT.…”
Section: Introductionmentioning
confidence: 99%
“…A national orthognathic audit was undertaken during 2017-2018 of acceptance criteria for treatment and information provided to patients before their treatment (Ireland et al, 2019). A total of 69 hospitals submitted evidence, including Whipps Cross.…”
Section: Political Background To the Second Pilot Phase (2014-2017)mentioning
confidence: 99%